LLANVIRNIAN (ORD.) IRON OOIDS IN BALTOSCANDIA: ELEMENT MOBILITY, REE DISTRIBUTION PATTERNS, AND ORIGIN OF THE REE - Sturesson U. (My University, 1995)
The chemical and mineralogical compositions of Llanvirnian (Ordovician) iron and associated phosphate ooids from Sweden, Estonia and Russia have been examined. The oolites are generally thin and lean (mud supported), and dominated by Feoxyhydroxide (goethite, limonite) ooids. One Swedish oolite contains a mixture of chamosite, goethite and hematite ooids, and it is suggested that the two latter types were derived from chamosite ooids by early diagenetic alteration. The REE distribution patterns were unaffected by these reactions. All ooids in the area show a typical negative Eu anomaly inherited from the source material. Major-and minor-element contents in limonite and chamosite ooids are similar, whereas their REE patterns are different. Limonite ooids have a LREE ratio from 1 to 2.4, and chamosite ooids from 3 to 5. The amounts of REE in the ooids are strongly dependent on the amount of phosphate.
Keywords: Ordovician; Paleozoic::Ordovician; Палеозой::Ордовикская